Penerapan Model Cooperative Learning Tipe Teams Games Tournament (TGT) Untuk Meningkatkan Kemampuan Membaca Bahasa Arab Siswa Kelas VIII H Semester Genap Di MTs Darul Huffazh Pesawaran - Yuyun indrawati; Nurkholis; Heriansah (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2022)
Impact is that students often have difficulty understanding Arabic lessons and many of their reading abilities do not meet the Minimum Competency Standards (KKM), while the formulation of the problem in this study is "How to Apply Cooperative Learning Model Types of Teams Games Tournament (TGT) in the ability to read Arabic learning in class VIII H MTs Darul Huffazh?” Is the use of the application of the Teams Games Tournament (TGT) Cooperative Learning Model to improve reading skills in Arabic learning. while the purpose of this study is to find out how the application of the Teams Games Tournament (TGT) Cooperative Learning Model can improve students' reading skills towards learning Arabic in class VIII H MTs Darul Huffazh Gedong Tataan Pesawaran Lampung, and this research was carried out in three cycles using the research method. Class Actions (CAR) conducted at MTs Darul Huffazh Gedong Tataan Pesawaran Lampung, based on the reading ability that the researchers had carried out, it was concluded that there was an increase in the results of the pre-test to the first cycle, obtaining an average value of 69.58 while in the first cycle it was obtained the average value of 76.04 in the second cycle obtained an average value of 83.95, so the increase in the pre-test to the first cycle reached 6.46 in the first cycle to the second cycle reached 1.46 in the second cycle to the third cycle it reached 6, 46.